Seroprevalence of Asymptomatic Leishmania donovani among Laborers and Associated Risk Factors in Agricultural Camps of West Armachiho District, Northwest Ethiopia: A Cross-Sectional Study - Animen Ayehu; Yibeltal Aschale; Wossenseged Lemma; Animut Alebel; Ligabaw Worku; Ayalew Jejaw; Abebe Genetu Bayih (Journal of Parasitology Research)
Background. Visceral leishmaniasis (VL, also called kala-azar) is a public health problem in Ethiopia, especially in sesame and sorghum growing areas. Compared to other populations, labor migrants are the most exposed. Knowing the seroprevalence of Leishmania donovani and associated risk factors is essential to design appropriate control measures. The main aim of this study was to assess the seroprevalence of asymptomatic L. donovani among laborers and associated risk factors in agricultural camps of West Armachiho district, Northwest Ethiopia. Therefore, this study was conducted to know the seroprevalence and associated risk factors of L. donovani infection. Method. A cross-sectional study was conducted among 185 laborers from October to December 2017. A simple random sampling technique was used to select study participants from selected agricultural camps. After obtaining written informed consent, data were collected using a structured pretested Amharic version questionnaire using the interview technique. A single finger prick blood sample was collected from the study participants and the blood samples were subjected to the serological diagnostic method using the rk39 kit. The multivariable logistic regression model was used to identify risk factors associated with L. donovani infection. Result. Among 185 participants examined using rk39, 14 (7.6%) were seroreactive for L. donovani. Leishmania donovani infection had a statistically significant association with sleeping under Balanites trees (AOR: 4.36, 95%CI: 1.186-16.06), presence of domestic animals near sleeping place (AOR: 4.68, 95% CI: 1.25-17.56), and lack of knowledge about VL transmission (AOR: 3.79, 95% CI: 1.07-13.47). Conclusion. Seroprevalence of asymptomatic L. donovani among laborers in agricultural camps of West Armachiho was low. Prevention measures and health education about risk factors that expose to L. donovani infection for the laborers are essential to prevent the spread of the disease.